2019
DOI: 10.3389/fimmu.2018.03135
|View full text |Cite
|
Sign up to set email alerts
|

CVID-Associated Tumors: Czech Nationwide Study Focused on Epidemiology, Immunology, and Genetic Background in a Cohort of Patients With CVID

Abstract: Background: Common variable immunodeficiency disorder (CVID) is one of the most frequent inborn errors of immunity, increased occurrence of malignancies, particularly lymphomas, and gastric cancers, has long been noted among CVID patients. Multifactorial etiology, including immune dysregulation, infections, chronic inflammation, or genetic background, is suggested to contribute to tumor development. Here, we present the results of the first Czech nationwide study focused on epidemiology, immunology and genetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
46
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 43 publications
8
46
0
1
Order By: Relevance
“…It is possible that we observed very selected cases, with serious manifestations, as we operated in a tertiary care Centre. However, this data agrees with findings by Kralickova et al, who identified ITP as a potential risk factor for cancer development in CVID patients [22]. In addition, the observation further suggests that the immune dysregulation underlying CVID may promote malignant occurrence [22].…”
Section: Discussionsupporting
confidence: 92%
“…It is possible that we observed very selected cases, with serious manifestations, as we operated in a tertiary care Centre. However, this data agrees with findings by Kralickova et al, who identified ITP as a potential risk factor for cancer development in CVID patients [22]. In addition, the observation further suggests that the immune dysregulation underlying CVID may promote malignant occurrence [22].…”
Section: Discussionsupporting
confidence: 92%
“…KDM5A is associated with many non-cancer diseases, such as congenital heart disease (CHD) [ 82 ] and bacterial, viral, or parasitic infection [ 79 , 83 , 84 ]. It also mediates renal failure in lipopolysaccharide-induced sepsis of mice [ 85 ].…”
Section: The Roles Of Kdm5a In Non-cancer Diseasementioning
confidence: 99%
“…Conversely, CVID patients with autoimmune cytopenias had a higher frequency of CVID-associated non-infectious complications, including granulomatous and lymphoproliferative disease, as well as organ-specific autoimmune disease, but interestingly, not systemic autoimmunity (26). In a recent study of a 295 patient CVID cohort in the Czech Republic, immune thrombocytopenic purpura (ITP) was identified as a risk factor for malignancy, with over a 3-fold increase compared to those without ITP (27). Splenomegaly was also more common in patients with autoimmune cytopenias and was found to share some immunophenotypic characteristics, but the pathophysiology of this link is still not clearly understood (28).…”
Section: Overview Of Autoimmune Disease In Common Variable Immunodefimentioning
confidence: 99%